Aboriginal partnerships for sustainable 2010 Olympic and Paralympic Winter Games: a framework for cooperation - Dunn, Catharine Hilary (2007)
Indigenous peoples? participation has historically been an afterthought to Olympic Games Bidding and Organizing Committees. For the first time in Olympic Games history, Indigenous peoples have been recognized and included as Official Partners in the planning and hosting of the 2010 Winter Games. This research explores partnership developments between the Four Host First Nations - the Lil?wat, Musqueam, Squamish and Tsleil-Waututh, on whose traditional and shared traditional territories the 2010 Winter Games will be held ? and the 2010 Bid Corporation/VANOC. The findings and resulting framework suggest that successful partnerships between Indigenous communities and Olympic Organizing Committees need to be formalized in the bid phase and enhanced during the organizing and hosting phases. The research also suggests that the IOC has an opportunity to promote partnership development between Indigenous peoples and future Olympic and Paralympic Games organizers as a result of lessons learned surrounding the 2010 Winter Games.